Study On Morphometric, Meristic And Growth Patterns Of Anabas Testudineusin Channelof Oil Palm Plantation Left Tapung River Bencah Kelubi Village Tapung Kiri Subdistrict Riau Province - Situmorang, Dina; Putra, Ridwan Manda; Efizon, Deni (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2014)
The study aims to understand morphological and meristical characteristics, relative growth and condition factor of Anabas testudineus living in Channel of oil Palm Plantation Left Tapung River Bencah Kelubi Village Tapung Kiri Subdistrict Riau Province. The study has been conducted on Januari to Maret 2014. The study used survey methods.Sampling was done five times in three month. Theresults shownthere were 125fishes (60-162 mm TL and 3-92 gr) which collected and measured. There are seven characters that will be calculated meristic and 27 morphometric characters that will be measured in this study. Meristical characteristics of fins were as follows D.XVII-XIX,7-9, P.13-15, V.1.5, A.IX-X,9-11, C.16-20. Twenty seven morphological characteristics were measured and to understand the growth pattern, each character length was compared with Total Length (TL) and was reflected as percent of the TL.The relative growth patterns of the morphological characteristic measured is the characteristic growing faster than that of the TL. Lenght-weight relationship shown that A. testudineus male growing isometric andA. testudineus female allometric positive (male b=2,837, and female 3,156).The water quality shown temperature 28 – 300C, pH 6-7, DO 0,9 – 2,3 mg/L, CO2 18,2-20,9 mg/L, transparency 5-7cm, depth 15-20 cm and all water quality still support the life of fish.Key words : Anabas testudineus, Channel of Oil Palm Plantation Left Tapung River, morphological characteristic, meristical characteristic